Perceptions of elite coaches and sports scientists of the research needs for elite coaching practice - Williams, S. J.; Kendall, L. (Journal of Sports Sciences, 2007)
A major objective of sports scientists and elite coaches is the enhancement of athletic performance. Despite this common goal, there is a general perception that research in sports science does not meet the needs of coaches. A study using survey and interview examined the perceptions of elite coaches and sports science researchers in Australia regarding the research needs of elite coaching. Congruence was found between coaches and researchers regarding research practice at the elite level. Both groups held common perceptions on the importance and application of research, the methods by which research questions are determined, and the qualities valued in elite coaches and sports science researchers. However, elite coaches perceived a need for more research in the area of sports psychology, dissemination of research findings via coaching clinics and sports-specific magazines, and the use of more appropriate "lay" language in information dissemination.